Evolving Practices: Admissions Policies in Ontario Teacher Education Programs - Holden, Michael; Kitchen, Julian (Canadian Journal of Education/Revue canadienne de l'éducation, 2016)
This study investigated the admissions practices of Ontario’s teacher education programs during the 2014–2015 and 2015–2016 academic years. Data were gathered from 15 institutions via online resources and collaborative conversations with stakeholders at each institution. The findings identify that academic averages are used by every Ontario university as a measure of cognitive skills, while non-cognitive written statements and references are used by a majority of institutions. A majority of programs also articulate explicit equity admissions policies. These findings represent the first study of Ontario admissions in the wake of Regulation 283/13, and the first Ontario admissions study to augment online data with province-wide stakeholder input. This research offers a thorough, current overview of admissions practices that may be used to inform policymaking in Ontario teacher education, and serve as a helpful resource to other ITE programs outside of Ontario.